Differential Associations Between Distinct Components of Cognitive Function and Mobility: Implications for Understanding Aging, Turning and Dual-Task Walking - Sunderaraman, Preeti; Maidan, Inbal; Kozlovski, Tal; Apa, Zoltan; Mirelman, Anat; Hausdorff, Jeffrey M.; Stern, Yaakov (Frontiers in Aging Neuroscience, 2019)
Objective: Cognition and mobility are interrelated. However, this association can be impacted by the specific facets of cognition and mobility that are measured, and further by the different task conditions, single- versus dual-task walking, under which these associations are evaluated. Systematically studying the multiple facets of cognitive-mobility associations under both the task conditions is critical because both cognition and mobility change with age and pose significant risks associated with falls, morbidity, and disability. Methods: Using a cross-sectional, prospective study design, data from 124 healthy adults (mean age (SD) = 61.51 (11.90); mean education (SD) = 15.94 (2.18)) was collected. A comprehensive battery of cognitive tests was administered, and gait was assessed using a small, lightweight, three-axis accelerometer with a gyroscope. Analytical Plan: Data was transformed, and only relatively strong relationships survived after strict statistical criteria adjusting for multiple comparisons was applied. Spearman rho correlation coefficients were used to examine the matrix of correlations between the cognitive-motor variables while adjusting for age and gender. Results: Executive functions, processing speed, and language were associated with distinct facets of variability, pace, asymmetry, especially under the dual-task walking condition. Both turns and transitions were also associated with cognition during the Timed Up and Go task. Conclusion: Our results extend converging evidence for the involvement of executive functions and processing speed in specific aspects of mobility, along with the role of language. The study has important implications for aging in terms of both assessment and rehabilitation of cognition and gait as well as for the emerging dual-tasking theories and the role of the neural pathways involved in mobility.